A cross-sectional multicentre qualitative study exploring attitudes and burnout knowledge in intensive care nurses with burnout - Friganović Adriano; Kurtović Biljana; Selič Polona (Sciendo, 2020)
Although nurses in intensive care units (ICUs) are exposed to prolonged stress, no burnout prevention policy has yet been established. This study aims to determine the attitudes and "sense" of knowledge of burnout in nurses with burnout.